Challenges And Strategies For Implementing Performance-Based Capitation In Indonesian Community Health Center : A Scoping Review - Oki Ino Fatwa Firdhaus; Ayun Sriatmi; Antono Suryoputro (Eduvest - Journal of Universal Studies, 2024)
This study examines the implementation and challenges of performance-based capitation (KBK) at Community Health Centers (Puskesmas) in Indonesia, as a part of the National Health Insurance Program, aiming to improve the efficiency and quality of primary health services. Despite its potential, the implementation of KBK faces various challenges including inadequate human resources, limited infrastructure, and insufficient monitoring systems. The study uses a scoping review framework based on the Public Health Care Monitoring Conceptual Framework by WHO, analyzing 11 selected studies from 2021 to 2024. Findings indicate that internal factors such as management capacity, health worker competence, and organizational culture significantly impact the effectiveness of KBK. External factors like local government support, funding policies, and infrastructure availability also play crucial roles. Technological barriers, particularly in remote areas, hinder optimal policy implementation. The study emphasizes the need for clear regulations, consistent policy dissemination, and effective monitoring to ensure successful KBK implementation. Recommendations include strengthening leadership, training health workers, improving infrastructure, and enhancing digital health technology utilization. These strategies aim to optimize resource allocation, enhance service access, and improve patient satisfaction in Indonesia’s primary health care system.